THE PEACE MOVEMENT TO END THE RIVALRY BETWEEN FOOTBALL SUPPORTERS OF PSS SLEMAN AND PSIM YOGYAKARTA - Brataatmaja, Decaesar Dewa (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2023)
Football in Indonesia is a dynamic popular culture that is associated with the emotional instability of its fans. Fanaticism is something that is believed to give a greater form of love and zest for life for a person or group, while on the other hand, rivalry can also be said to be a form of anarchism of supporters. The purpose of this study was to find out the form of communication from the virtual community of two supporters in Yogyakarta in realizing better football. This research is qualitative studies that using netnography and virtual observation as the method. The rivalry between PSS Sleman and PSIM Yogyakarta supporters is a form of fanaticism or an exaggerated form of love. This research has a point that makes them reflect on each other, namely the Kanjuruhan tragedy which caused 135 lives to be lost. This made Sleman and Yogyakarta supporters reflect and produce a form of virtual communication that builds and leads to a peace movement. It is seen from this research that adaptive structuring occurs both within the scope of individuals and groups of supporters that an adult form of love for football is a peace. In the form of transactional analysis, it is also seen that the form of change or maturity of these supporters is formed based on the awareness and willingness of all layers of Sleman and Yogyakarta supporters so that peace is created. Keywords: Fanaticism & Rivality; Peace; Virtual Communities; Netnography.